Ejecución presupuestaria en el periodo 2017 - 2018 de la empresa pública municipal de agua potable y alcantarillado de Ventanas - Chávez Mancheno, Lady Diana (2020)
Through the development of the theme: BUDGETARY IMPLEMENTATION IN THE PERIOD 2017 - 2018 IN THE MUNICIPAL PUBLIC COMPANY OF DRINKING WATER AND WINDOW SEWER has the objective of determining the novelties presented in the budget schedules during its execution and the bases that support this research were taken of the INSTRUCTION FOR THE DISCONCENTRATION OF CLASSES OF ACCOUNTING RECORDS (PHASE 4) LOW AND COMPENSATION ruled by the MINISTRY OF FINANCE. This directed by the line of investigation of Financial Management and Social Commitment in turn the deductive method was used since it is the one that allows me to use the observation technique, the main problem of the selected topic, is based on the novelties found in the income revenue schedules corresponding to the period 2017 - 2018, for the reason that a higher value accrued than that codified which this event directly affects the budget surplus presented in the Statement of Budget Execution.